A Short and Efficient Enantioselective Synthesis of (+)‐(2S, 3S, 5S)‐epi‐Muscarine. Issue 21 (5th June 2020) - Gehlawat, Anju; Prakash, Ranjana; Kumar Pandey, Satyendra
Abstract: A short, efficient and novel enantioselective general approach for the synthesis of muscarine alkaloid and its application to the asymmetric synthesis of epi ‐muscarine from readily available ( R )‐PMB glycidyl ether as starting material is described. Key transformations include Sharpless asymmetric dihydroxylation (AD), regioselective epoxide ring opening and intramolecular SN 2 cyclization. Abstract : An efficient and novel general method for asymmetric synthesis of muscarine alkaloids and its application to the total synthesis of (+)‐ epi ‐muscarine from ( R )‐PMB glycidyl ether as starting material is presented. Key transformations include Sharpless asymmetric dihydroxylation (AD), regioselective epoxide ring opening and intramolecular SN 2 cyclization.